2002
DOI: 10.1021/jo020446t
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Syntheses of Benzothiazepines as Antagonists for the Mitochondrial Sodium−Calcium Exchanger:  Potential Therapeutics for Type II Diabetes

Abstract: Type II diabetes mellitus is a chronic metabolic disorder that can lead to serious cardiovascular, renal, neurologic, and retinal complications. While several drugs are currently prescribed to treat type II diabetes, their efficacy is limited by mechanism-related side effects (weight gain, hypoglycemia, gastrointestinal distress), inadequate efficacy for use as monotherapy, and the development of tolerance to the agents. Consequently, combination therapies are frequently employed to effectively regulate blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…The isosteric analogue of CGP37157 where chlorine at position orto of the phenyl ring (C2′) has been replaced by a methyl group (Figure 1), namely, ITH12505, was synthesized according to the experimental procedure described, 36 obtaining ITH12505 with a 58% yield, showing analytical and spectral data according to the literature. 36 Culture of Chromaffin Cells. Adrenal glands were obtained from the city slaughterhouse, under the supervision of the local veterinary service.…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The isosteric analogue of CGP37157 where chlorine at position orto of the phenyl ring (C2′) has been replaced by a methyl group (Figure 1), namely, ITH12505, was synthesized according to the experimental procedure described, 36 obtaining ITH12505 with a 58% yield, showing analytical and spectral data according to the literature. 36 Culture of Chromaffin Cells. Adrenal glands were obtained from the city slaughterhouse, under the supervision of the local veterinary service.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Pei and co-workers have communicated the poor water solubility and short half-life of CGP37157. 36 In that paper, authors describe the efforts to synthesize CGP37157 derivatives, with improved pharmacokinetic profile and mNCX blocking activity, for their use as potential drugs for Type-II diabetes mellitus. Unfortunately, none of the new compounds improved that mNCX blockade elicited by CGP37157, while enhancement of the pharmacokinetic profile was not experimentally demonstrated.…”
Section: + Concentrations ([Camentioning
confidence: 99%
See 1 more Smart Citation
“…1), which has been widely used as a mitochondrial Na þ /Ca 2þ exchanger (mNCX) blocker (Chiesi et al, 1988;Pei et al, 2003). This compound and some of its analogues have shown a neuroprotective profile in several in vitro models of AD and stroke (Gonzalez-Lafuente et al, 2012;Nicolau et al, 2009Nicolau et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Another isomerization-RCM strategy was carried out by van Otterlo et al 29 who reported that the synthesis of benzothiazocine dioxide from the corresponding sulfone was carried out in high yield. In an alternative strategy, Lilly et al 30 reported a simple protocol for the synthesis of various benzo-1,4-thiazocines via intramolecular cyclization of acyclic-thioether substrates. Mukherjee et al 31 have applied the same intramolecular cyclization methodology to the synthesis of 2,3,4,5-tetrahydro-2Hbenzo[b] [1,4]thiazocines by treatment of 3-(2-bromophenylthio)propan-1-amines (arenes) with lithium diisopropylamide (LDA).…”
Section: Introductionmentioning
confidence: 99%